Penentuan Faktor Daya Saing Industri Seafood Menggunakan Five Forces Analysis - Hanafi, Rosmalina; Mendong, Musmiana; Parenreng, Syarifuddin (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2019)
The seafood industry has experienced a gradual increase in exports each year which has an impact on the high value of competitiveness in companies. PT. Nirvana Niaga Sejahtera is a seafood industry engaged in the tuna commodity export trade. The concept of competitiveness analysis and the best supplier selection used is the Five Forces Analysis concept based on five strength indicators which are incoming company threats, buyers, consumers, substitute product manufacturers, analysis of supplier strengths and AHP methods use expert choice 11 software to produce the company's best supplier. The results of the Five Forces Analysis model show that investor threats to new companies and the number of similar companies can affect the bargaining power of buyers and the quality of suppliers. The selection model using AHP produces alternative for supplier that are Supplier A (Toli-Toli) 0.385, Supplier B (Kendari) 0.322, Supplier C (Ternate) 0.279.